Cracking The Impulsive Shopping Code: (An Intriguing Exploration Of Indomaret In Huko-Huko Village) - Jeanette Tangalayuk; Almansyah Rundu Wonua; Hanif Kurniadi (Jurnal Mahasiswa Kreatif, 2023)
This study seeks to investigate the relationship between discounts and product display in influencing impulsive buying among customers at Indomaret in Huko-Huko Village. The study encompassed all customers of Indomaret in Huko-Huko Village, with a sample of 110 respondents chosen using purposive sampling. The research data was analyzed using the Structural Equation Modeling (SEM-PLS) method. The results of the study indicate that discounts have a positive and statistically significant impact on impulsive buying, and product display also has a positive and significant influence on impulsive purchases